2017
DOI: 10.1111/jfpp.13501
|View full text |Cite
|
Sign up to set email alerts
|

Sodium tripolyphosphate inhibits the formation of lysinoalanine in heat-treated whey protein

Abstract: Heat treatment is a common method to improve certain functional properties of whey protein, whereas this process is usually accompanied with the formation of lysinoalanine (LAL), which may reduce the protein nutritional value and even cause safety concerns. This study aimed to investigate the effect of the protein content (8–10%, wt/vol), pH (7.5–8.5), heating temperature (70–85 °C), and time (5–20 min) on the degree of LAL generation in thermal treatment of whey protein concentrate (WPC) solutions. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The increase in LAL with increase in alkali concentration until a zenith is reached, followed by a rapid decline confirm the formation and obliteration of LAL with increase in alkali concentration as reported in other studies (Zhao, Luo, Li, Xu, & Tu, 2016). The formation of LAL has been heavily linked to elevation of temperature and pH of extraction medium (Cattaneo, Stuknytė, Masotti, & De Noni, 2017;Liu, Zhao, & Guo, 2017), however, the major influence on the formation of LAL in this study can only be attributed to variations in pH due to variations in alkali concentration. Friedman (1999) reported the notification of LAL in soybean protein at pH 9.0, which increased until pH 12.5 before finally decreasing at pH 13.9.…”
Section: Effect Of Alkaline On Lal Generationsupporting
confidence: 87%
“…The increase in LAL with increase in alkali concentration until a zenith is reached, followed by a rapid decline confirm the formation and obliteration of LAL with increase in alkali concentration as reported in other studies (Zhao, Luo, Li, Xu, & Tu, 2016). The formation of LAL has been heavily linked to elevation of temperature and pH of extraction medium (Cattaneo, Stuknytė, Masotti, & De Noni, 2017;Liu, Zhao, & Guo, 2017), however, the major influence on the formation of LAL in this study can only be attributed to variations in pH due to variations in alkali concentration. Friedman (1999) reported the notification of LAL in soybean protein at pH 9.0, which increased until pH 12.5 before finally decreasing at pH 13.9.…”
Section: Effect Of Alkaline On Lal Generationsupporting
confidence: 87%
“…As shown in Table 2, the percentage (g/100 g) of cysteine (Cys), methionine (Met), and lysine (Lys) decreased significantly after the combined pH 12 shift and heating treatment. Under such treatment conditions, free Cys and those derived from disulfide bond hydrolysis formed dehydroalanine and then reacted with the ε-NH 2 groups of lysine side chains, 32 thus explaining its moderate loss and the resulting formation of LAL. Friedman et al 26 and Zhang et al 29 found that Cys residues were most labile to alkali.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Rapeseed protein isolate (RPI) has great economic prospects due to its high nutritional value and availability of the meal (raw material) from which the protein is isolated. , However, RPI often needs to be modified to improve its poor functional properties to meet the needs of the food industry. pH shift treatment, which can induce the partial unfolding and refolding of the protein molecules under an extremely acidic or alkaline condition, is an effective means of modifying the functional properties of plant proteins, such as solubility, emulsification activity, and stability .…”
Section: Introductionmentioning
confidence: 99%